Creative Thinking: The Development of Lifelong Learning With the Principle of Andragogy for The Elderly Group in Northern Thailand - Sirisyos Kijmongkolvanich; Siriphong Sirisawat; Songwut Egwutvongsa (My University, 2024)
The purpose of this research was to compare the learning outcomes of teak furniture production by applying the andragogy principle and studying the learning factors in teak furniture development in older groups. The population consisted of 110 local technicians of the Phrae Wood Products Trade Association, Phrae Province, Thailand. For this study, the sample group consisted of 86 local technicians aged 55 years and older who were selected by stratified sampling, and structured questionnaires were used as the research tool and analyzed using the paired sample t-test, exploratory factor analysis (EFA) and multiple regression analysis. Furthermore, it was found that both pre-training and post-training knowledge were correlated (Sig. = 0.000) in a positive direction (r = 0.799) with statistical significance at a level of.05 Additionally, when analyzed with EFA, it was found that there were factors that affect the learning efficiency of the elderly in three aspects (KMO = 0.788): 1) the creativityprocess, 2) the development of skills, and 3) the enhancement of knowledge in business expansion. All three factors were analyzed by multiple regression analysis. As a result, it was found that R = 0.836, R2 = 0.700, and Adj R2 = 0.689 according to the standard regression equation that was = .407(X1) + .323 (X2) + .596(X3).
Keywords: Andragogy; Exploratory factor analysis; Sample (material); Stratified Sampling; Creativity in Education and Neuroscience